Field evaluation of effectiveness of subsurface porous pipe irrigation system on sweet corn (Zea mays L. saccharata) crop yield, water and fertilizer use efficiency - Prabhakar, Mamatha; Rank, H. D. (Journal of Tropical Agriculture, 2022)
A field study was conducted at RTTC, Junagadh Agricultural University, Gujarat during the Rabi 2018, to study the effectiveness of subsurface porous pipe irrigation system on crop production. Treatments consisted of twelve treatment combinations of two depths of installation [20 cm (D1) &30 cm (D2)], two lateral porous pipe lengths [30 m (L1) &45 m (L2)], three fertigation levels [F1-40 % (Recommended Dose of Fertilizer-RDF), F2-70 % RDF and F3-100 % RDF]) and a control (surface drip irrigation with no fertigation),respectively. Soil hydraulic study performed after the installation of irrigation system ensured its suitabilityfor cultivation. Irrigation at 1.0 IW/CPE ratio [ratio of irrigation water (IW) and cumulative pan evaporation(CPE)] was maintained as same in all treatments including the control treatment. Interaction effect of installed depth, length and three fertigation levels on corn ear yield (t/ha), fertilizer and water use efficiencies were studied. The experimental results showed that the highest corn yield, fertilizer use efficiency, water use efficiency, net return and Benefit-Cost ratio were recorded in the treatment F2L2D2 (70 % RDF supplied through a subsurface porous pipe of 45 m length, installed at 30 cm depth) which gave a net return of Rs. 3,50,282/ha/season.The study revealed that the subsurface porous pipe irrigation system is an efficient and economically feasible irrigation method for sweet corn cultivation in semi-arid regions.